Chloroplast dimorphism in leaves of Cabomba caroliniana (Cabombaceae) - Galati, Beatriz G. (2015)
Cabomba Aublet is useful as a genetic model of angiosperm evolution. Previous anatomical studies and preliminary light microscopic observations on C. caroliniana A Gray revealed the presence of dimorphic chloroplasts in both types of leaves, floating and submerged leaves. Leaf anatomy and chloroplasts ultrastructure were analyzed and compared. The chloroplast ultrastructure of the mesophyll and epidermal cells is different. Mesophyll chloroplasts have several plastoglobuli, large starch grains and grana formed by an average of 29 thylakoids. Epidermal chloroplasts are smaller, have grana formed by an average of 9 thylakoids and starch grains are occasional and smaller. A statistical analysis (t-test) was made to determine if differences between chloroplasts are significant. The ultrastructure of the epidermis chloroplast is similar to the one of sun leaves chloroplasts and the ultrastructure of the mesophyll chloroplast is similar to the one of shade chloroplast observed in other species.